Intermediate accounting 3 : based on PFRs, PASs and Philippine GAAP - Garcia, Vhinson Jay (Manila, Philippines : Real Excellence Publishing, 2023)
Well organized comprehensive illustrative simplified Philippine financial reporting standards (PFRSs) updated self -taught designated for OBE
Keywords: Accounting, Intermediate